Etiology, Frequency, and Clinical Outcomes of Myocardial Infarction After Successful Drug-Eluting Stent Implantation: Two-Year Follow-Up From the ADAPT-DES Study. (December 2015) - Dohi, Tomotaka; Maehara, Akiko; Witzenbichler, Bernhard; Rinaldi, Michael J.; Mazzaferri, Ernest L.; Duffy, Peter L.; Weisz, Giora; Neumann, Franz-Josef; Henry, Timothy D.; Cox, David A.; Stuckey, Thomas D.; Brodie, Bruce R.; et al.
Abstract : Background—: The frequency, causes, and impact of myocardial infarction (MI) after successful percutaneous coronary intervention have not been well studied. Methods and Results—: The Assessment of Dual Antiplatelet Therapy With Drug-Eluting Stents (ADAPT-DES) study was a prospective, multicenter registry study of 8582 patients undergoing successful drug-eluting stent implantation at 11 centers in the United States and Germany. After excluding 128 patients with periprocedural MI, we investigated the pathogenesis, frequency, and long-term consequences of non-periprocedural MI in 8454 patients. MI during 2-year follow-up developed in 263 patients (3.3%) at a median (25th and 75th percentiles) time of 318 (129, 503) days. The 263 MIs were subclassified as spontaneous MI (n=78; 29.7%), secondary or indeterminate MI (n=64; 24.3%), stent thrombosis–related MI (n=63; 24.0%), and in-stent restenosis–related MI (n=58; 22.1%). Multivariable predictors of MI included clinical and angiographic factors (acute coronary syndromes presentation, diabetes mellitus, current smoker, multivessel disease, treatment of an in-stent restenotic lesion), laboratory findings (low baseline hemoglobin and reduced creatinine clearance), antiplatelet agent–related factors (higher on-treatment platelet P2Y12 receptor reactivity and premature thienopyridine discontinuation), and not being on a statin at discharge. Patients who experienced an MI during the follow-up period had significantly greater 2-year mortality than those without MI (17.3% [42 deaths] versus 3.4% [265 deaths], P <0.001). By multivariable analysis, the adjusted hazard ratio (95% confidence interval) for subsequent mortality during follow-up was 2.17 (1.06, 4.45) in patients with versus without a non-periprocedural MI ( P =0.03). Conclusions—: The occurrence of a non-periprocedural MI within 2 years after successful drug-eluting stent implantation is relatively infrequent, but has numerous etiologies and is significantly associated with subsequent mortality. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00638794. Abstract : Supplemental Digital Content is available in the text.